Working Toward Equality: Putting Vision into Practice - Hendy, John (Unions Matter: Advancing Democracy, Economic Equality, and Social Justice, 2014)
Explores the disconnect between the right to equality being praised as reflecting the dreams, hopes, and aspirations of Canadian society, and its elusiveness in practice. [The author] also reflects on how labour and progressive movements can measure success in advancing equality in law. --Introduction
Keywords: Canada; Canadian Foundation for Labour Rights; Democracy; Employee rights; Equality; Labor movement; Labor unions; Social aspects; Social justice